Governing a multilevel and cross‐sectoral climate policy implementation network. (18th May 2021) - Wagner, Paul M.; Torney, Diarmuid; Ylä‐Anttila, Tuomas
Abstract: For national governments to meet their international climate change obligations they need to develop and implement plans that involve coordinating the actions of local, regional and national level actors from across multiple sectors. When this occurs, it can lead to the formation of a policy implementation network. Surprisingly, there is a limited understanding of the characteristics of the members of such networks, the structure of the multi‐level and cross‐sectoral ties among them, and about how they relate to how these networks are governed. This paper initiates the development of such knowledge by calculating a variety of network statistics to analyse the policy implementation network formed to carry out Ireland's signature climate policy— The Climate Action Plan 2019 . Results show that national level actors dominate, and that cross‐level and cross‐sectoral collaboration are limited. The plan is governed by a network administrative organisation (NAO), with the Department of the Taoiseach (Irish Prime Minister) filling the role. How the network is structured and governed increases the likelihood that the network will be stable, have a unity of purpose and be able to meet its objectives. However, the dominance of national‐level actors and its centralized structure are likely to make it challenging for the NAO to gain the support of local‐level actors. This paper's methodological approach can be applied in other contexts to understand inter‐actor relations and how these affect the responsibilities, challenges and opportunities of the actors involved in the implementation of a national environmental policy.